CAPITAL STRUCTURE AS A STRATEGIC MODERATOR OF THE FINANCIAL PERFORMANCE–FIRM VALUE RELATIONSHIP: EVIDENCE FROM IDX-IC EXTRACTIVE ENERGY COMPANIES IN INDONESIA - Erdy Riahman Damanik; Sukiranto; Atika Purnamasari; Merida (Jurnal Widya Akuntansi dan Keuangan, 2026)
This study investigates the effect of financial performance on firm value, with capital structure serving as a moderating variable, in mining and extractive energy companies classified under the Indonesia Stock Exchange Industrial Classification (IDX-IC) during the 2020–2024 period. The research aims to address the existing literature gap regarding the moderating role of capital structure in the relationship between financial performance and firm value within capital-intensive industries characterized by commodity price volatility and global economic uncertainty. A quantitative research approach was employed using a purposive sampling technique, resulting in a final sample of 16 companies or 80 firm-year observations. The data were analyzed using Statistical Package for the Social Sciences (SPSS) version 25, including classical assumption tests, t-test, F-test, coefficient of determination (Adjusted R²), and Moderated Regression Analysis (MRA). The findings reveal that financial performance, measured by Return on Assets (ROA), has a positive and significant effect on firm value, measured by Tobin's Q. Furthermore, capital structure, proxied by the Debt-to-Equity Ratio (DER), significantly strengthens the relationship between financial performance and firm value. These findings indicate that an optimal capital structure enhances the positive impact of profitability on firm value by improving investor confidence in the company's financial performance and financing decisions.